Pharmacological action of Angelica sinensis polysaccharides: a review - Ren, Chunzhen; Luo, Yali; Li, Xiaojuan; Ma, Like; Wang, Chunling; Zhi, Xiaodong; Zhao, Xinke; Li, Yingdong (Frontiers in Pharmacology, 2025)
Angelica sinensis, a traditional Chinese herbal medicine and food, which has a long history of clinical application, is used to improve health conditions and treat various diseases. Angelica sinensis polysaccharides (ASP), the main active component of this traditional Chinese medicine, have multicomponent, multitarget characteristics and very broad pharmacological activities. They play important roles in the treatment of several diseases. In addition, the effect is significant, which may provide a more comprehensive database and theoretical support for applying ASP in the treatment of disease and could be considered a promising candidate for preventing disease. This review summarizes the research progress on the extraction, chemical structure, pharmacological effects, and mechanisms of ASP and its derivatives by reviewing relevant national and international literature and provides comprehensive information and a reliable basis for the exploration of new treatment strategies involving botanical drugs for disease therapy. Literature information was obtained from scientific ethnobotany and ethnomedicine databases (up to September 2024), mainly from the PubMed, Web of Science, and CNKI databases. The literature has explored the extraction, purification, structure, and pharmacological effects of Angelica sinensis polysaccharides. The search keywords for such work included “Angelica sinensis” or “Angelica sinensis polysaccharides,” and “pharmacological effects,” “extraction” and “structure.” Multiple studies have shown that ASP has important pharmacological effects, such as antitumor, anemia-improving, anti-inflammatory, antioxidative, immunomodulatory, hepatoprotective, antifibrotic, hypoglycemic, antiradiation, and antiviral effects, the mechanisms of which appear to involve the regulation of inflammation, oxidative stress, and profibrotic signaling pathways. As a natural polysaccharide, ASP has potential applications as a drug. However, further research should be undertaken to clarify the unconfirmed regulatory mechanisms, conduct standard clinical trials, and evaluate the possible side effects. This review establishes a theoretical foundation for future studies on the structure, mechanism, and clinical use of ASP.